2022
DOI: 10.1242/bio.058899
|View full text |Cite
|
Sign up to set email alerts
|

Actin cytoskeleton in angiogenesis

Abstract: Actin, one of the most abundant intracellular proteins in mammalian cells, is a critical regulator of cell shape and polarity, migration, cell division, and transcriptional response. Angiogenesis, or the formation of new blood vessels in the body is a well-coordinated multi-step process. Endothelial cells lining the blood vessels acquire several new properties such as front–rear polarity, invasiveness, rapid proliferation and motility during angiogenesis. This is achieved by changes in the regulation of the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 208 publications
1
5
0
Order By: Relevance
“…Meanwhile, the diabetic cells decreased the formation of stress fibers and focal adhesions under anisotropic topographies. In this regard, FAKs are intimately involved in robust cell adherence to materials surfaces, cell survival, and long-lasting endothelial propagation [ 45 , 47 ], information that supports our outcomes of metabolic activity ( Figure 2 ). The current trends following our results are in accordance with the FE-SEM shreds of evidence of the initial AThEC adhesion at 4 h, as depicted in Figure 4 .…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Meanwhile, the diabetic cells decreased the formation of stress fibers and focal adhesions under anisotropic topographies. In this regard, FAKs are intimately involved in robust cell adherence to materials surfaces, cell survival, and long-lasting endothelial propagation [ 45 , 47 ], information that supports our outcomes of metabolic activity ( Figure 2 ). The current trends following our results are in accordance with the FE-SEM shreds of evidence of the initial AThEC adhesion at 4 h, as depicted in Figure 4 .…”
Section: Resultssupporting
confidence: 65%
“…The findings may be elucidated by the supported cytoplasmic crisscross pattern of stress fibers organization which are involved in cellular mobility, proliferation, and mitochondrial activity [ 44 ]. The retroactive vinculin converging within those filaments develops consistent focal adhesions strongly associated with the phosphorylation of the focal adhesion kinase (FAKs) and the subsequent signaling pathway [ 45 ]. Interestingly, our current results align with a previous work of damaged endothelial cells isolated from human diabetic artery walls cultured over micro- and nano-patterned polydimethylsiloxane surfaces [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…31 Also, the constant remodeling of the actin cytoskeleton is essential for ECs migration in angiogenesis. 32 Thus, we test the expression of CD31 and F-actin characterized by immunofluorescence (IF) staining (Figure 2D,E). IF staining was performed after treatment of HUVECs with BPNS for 0, 1, 3, and 7 days.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that observed lumens accounts for 5–10 ​μm diameter, suggesting that the luminal structures are made up by either one or two endothelial cells folding together into lumen shape. Actin is a highly dynamic and mechanosensitive cytoskeletal component in endothelial cells, that undergoes constant remodeling into filopodia, lamellipodia and stress fibers for facilitating cell migration during angiogenesis [ 37 ]. Previous studies have shown a difference of 1.5 fold in actin production among encapsulated HUVECs within stiffer hydrogels compared to relatively softer ones [ 38 ].…”
Section: Resultsmentioning
confidence: 99%